2022
DOI: 10.1097/spv.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

In-Person Versus Video Preoperative Visit: A Randomized Clinical Trial

Abstract: Importance This study further supports virtual visits for gynecologic preoperative care.Objectives The objective of this study was to determine if preoperative video visits are noninferior to in-person visits in pelvic reconstructive surgery. Secondary objectives are as follows: patient satisfaction, convenience, visit duration, total perioperative visits, and patient travel time/distance. Study Design Noninferiority randomized-controlled trial of patients undergoing pelvic reconstructive surgery randomized to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In several small RCTs, there was no difference in patient satisfaction between virtual and in-person visits for gynecologic surgical offices [7,8 ▪ ]. A 2023 noninferiority RCT of office compared with video preoperative visits found that patient reported greater convenience and satisfaction with video preoperative visits [9 ▪▪ ]. Although video visits were of shorter duration for patients, they were of the same duration for providers.…”
Section: Preoperative Visitsmentioning
confidence: 99%
“…In several small RCTs, there was no difference in patient satisfaction between virtual and in-person visits for gynecologic surgical offices [7,8 ▪ ]. A 2023 noninferiority RCT of office compared with video preoperative visits found that patient reported greater convenience and satisfaction with video preoperative visits [9 ▪▪ ]. Although video visits were of shorter duration for patients, they were of the same duration for providers.…”
Section: Preoperative Visitsmentioning
confidence: 99%